129Xe NMR studies of morphology and accessibility in porous biochar from almond shells. Issue 105 (1st November 2016) - Farina, M.; Mauri, M.; Patriarca, G.; Simonutti, R.; Klasson, K. T.; Cheng, H. N.
Abstract : 129 Xe NMR EXSY plot demonstrating pore connectivity in sustainable almond shell biochar generated from anaerobic thermal activation and rainwater washing. Abstract : Micro and mesoporous materials are often used in catalysis, purification, composite filler, and other applications. Almond shell is an important agricultural byproduct that can be transformed to microporous and mesoporous carbon. In this work, we produced biochar from almond shell using a thermal treatment procedure in an inert atmosphere and characterized the pores with nitrogen adsorption, environmental SEM, and 129 Xe NMR. The latter technique differentiates adsorbed and nonadsorbed xenon and permits the correlation of different processing conditions with xenon adsorption and diffusivity. The relevance of removing the ash produced during the charring process has been included in the study. Moreover, the xenon exchange between meso- and micro-pores has been directly observed by 129 Xe NMR, demonstrating that after ash removal by water the materials have high accessibility of the pores by external fluids, thus increasing the usefulness as filtration or adsorption material.